2022
DOI: 10.1029/2022ja030678
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Observations of Migrating Tides by Multiple Meteor Radars in the Equatorial Mesosphere and Lower Thermosphere

Abstract: We present the migrating tidal winds decomposed jointly from multiple meteor radars in four longitudinal sectors situated in the equatorial mesosphere and lower thermosphere. The radars are located in Cariri, Brazil (7.4°S, 36.5°W), Kototabang, Indonesia (0.2°S, 100.3°E), Ascension Island, United Kingdom (7.9° S, 14.4° W), and Darwin, Australia (12.3°S, 130.8°E). Harmonic analysis was used to obtain amplitudes and phases for diurnal and semidiurnal solar migrating tides between 82 and 98 km altitude during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…This change in the propagation conditions of DW1 explains the tidal variability in DW1 after SSWs and the modulation of DW1 by upwardly propagating planetary waves. Different to [22], an enhancement in DW1 was observed by meteor radars at low latitudes after the SSW of 2006 [24].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…This change in the propagation conditions of DW1 explains the tidal variability in DW1 after SSWs and the modulation of DW1 by upwardly propagating planetary waves. Different to [22], an enhancement in DW1 was observed by meteor radars at low latitudes after the SSW of 2006 [24].…”
Section: Introductionmentioning
confidence: 78%
“…The study of [22] utilised TIMED/SABER observations and found a reduction in the DW1 amplitude after SSW events. However, other studies predicted other responses of solar tides to SSWs (e.g., [24,45]). Thus, it makes sense to utilise the Aura series and to perform a composite analysis of 17 major SSWs and their influence on the deseasonalised, equatorial DW1 proxy.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, MFPRs can measure winds in the 60 to 80 km height region during the day. There are now more MLT (meteor) radars overall, and this has led to an improvement in the study of wave modes for planetary scale waves and tides (see e.g., [94]). However, the daytime radar winds in the 60 to 80 km height region previously provided by these radars are now not as generally available.…”
Section: Mean Wind Componentsmentioning
confidence: 99%
“…Atmospheric radio radars, such as medium frequency radars [1,2], meteor radars [3], and MST radars [4], play a significant role in the study of the dynamics and coupling of middle atmosphere and ground weather. They contribute to understanding the physics of atmospheric motion and sudden weather processes, establishing high-precision and high-resolution atmospheric models [5][6][7].…”
Section: Introductionmentioning
confidence: 99%